Influence of potassium, boron and zinc on growth, yield and fiber quality of two kenaf (Hibiscus caccabinus L.) varieties - Salih, Rabar Fatah (2016)
Kenaf (Hibiscus cannabinus L.) consists of two major parts: bast and core, that have greatly different properties in term of anatomy, mechanical, physical and chemical content. Due to these differences, both parts are to be refined separately and the behaviour of the bast fibre is the research of interest.In this research, different levels of potassium, boron and zinc were used to improve fiber quality, which aim to be utilized in biocomposite and textile industry. This research had been conducted in two field tests. The first field test involved three levels of potassium, three levels of boron and two levels of zinc on two kenaf varieties namely Fuhong FH-952 and kenaf variety 4383. Field test was laid out in randomized complete block design and three replications for each variety. Field test was conducted at Taman Pertanian Universiti, UPM, while second field test utilized optimum fertilizer level for FH-952 variety with various rate of zinc.In the first part of the project, all levels of potassium, boron, and zinc used showed an improvement on the growth, nitrogen content, fiber yield, morphological, and mechanical properties. Potassium at the rate of 100 kg/ha and 150 kg/ha while boron at the rate of 1.0 kg/ha and 1.5 kg/ha showed good effect on both varieties.Meanwhile, zinc was found effective only on morphological and mechanical properties for both varieties. FH-952 variety gave better performance than 4383 variety in terms of plant growth (plant height and stem diameter) except for leaf number. The maximum height achieved was 232.13 cm and stem diameter was 15.58mm when 150 kg/ha potassium was added without boron and zinc, which is about 30% of the increment. Nitrogen content showed highly effect on FH-952 variety when the percentage was increased with increasing of potassium rate. The nitrogen content value was recorded at 4.82% with potassium rate of 150 kg/ha without boron and zinc. Similar level of potassium 150 kg/ha showed an improvement in results fresh stem, dry stem, fresh bast, dry bast, fresh core and dry core, it was by 210.4,58.0, 60.2, 16.6, 150.2 and 41.4 ton/ha, respectively. Fiber length, fiber width and the cell wall thickness for the FH-952 variety were higher than 4383 variety when potassium was added at the rate of 150 kg/ha without boron and zinc, the value recorded was 2.53 mm, 23.22 μm and 7.73 μm, respectively. The highest value of lumen 9.67 μm and flexibility 47.76 were also recorded by FH-952 variety, when 100 kg/ha of potassium and 1.5 kg/ha boron applied. Variety 4383 has high value of tensile stress at 324.94 MPa and tensile modulus at 54.39 GPa when zinc was added at the rate of 5 kg/ha. However, fiber elongation of FH-952 is better than 4383 variety with 553.3 μm value when potassium, boron, and zinc were added at the rate of 100, 1.5 and 5.0 kg/ha, respectively.In the second part of the project, the morphological properties of FH-952 variety were also improved when zinc at a lower rate of 1.5 kg/ha was applied, while maintaining potassium and boron at the optimum levels. Fiber length and lumen width were 3.55 mm and 11.28 μm, respectively, when zinc was added at the rate of 1.5 kg/ha, while zinc at the rate of 3 kg/ha showed the best result of flexibility by 49.85.The overall results indicated that the 4383 variety is more suitable for biocomposite applications and the FH-952 is suggested to be applied in textile processing due to its morphological properties consistency.